(untitled) (Philosophy and Progress, 2016)
Japanese Religion, in general, refers to the multiplicity of religions in Japan. Different religious traditions coexist in Japan for centuries after centuries without breaking interreligious harmony among them. The present work especially focuses the Traditional Japanese Religions as major elements of culture that are basically a mixture of folk religions, early Shinto, Confucianism, Daoism and Buddhism. Shinto has been the indigenous tradition for over two thousand years until it was synthesized with foreign elements. Buddhism, Taoism and Confucianism have profoundly influenced the spiritual and socio-political life of the Japanese since 6th century AD. These religious traditions have long met, interacted and influenced each other and together formed the religious and cultural life of the Japanese people. Nonetheless, though the religious and intellectual life of the court was dominated by Buddhist and Confucian thought during the seventh and eighth centuries, Shinto remained the religion of the people and also became almost a part of the political machinery. Philosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014